2013
DOI: 10.1111/vco.12037
|View full text |Cite
|
Sign up to set email alerts
|

Combined zoledronic acid and meloxicam reduced bone loss and tumour growth in an orthotopic mouse model of bone‐invasive oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma is common in cats and humans and invades oral bone. We hypothesized that the cyclooxygenase-2 inhibitor, meloxicam, with the bisphosphonate, zoledronic acid (ZOL), would inhibit tumor growth, osteolysis and invasion in feline oral squamous cell carcinoma (OSCC) xenografts in mice. Human and feline OSCC cell lines expressed cyclooxygenase (COX)-1 and 2 and the SCCF2 cells had increased COX-2 mRNA expression with bone conditioned medium. Luciferase-expressing feline SCCF2Luc cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
0
11
0
2
Order By: Relevance
“…Feline oral SCC (either in clinical patients, cell lines or immunohistochemical studies) has been used as a model for tumor hypoxia (which may be targeted to improve responses to chemo- or radio-therapy) [ 57 ] and mechanisms and treatment of bone invasion [ 51 , 58 , 59 , 60 , 61 ]. EGFR is a druggable target in HHNC [ 42 ], and the feline and human EGFR sequences are highly homologous [ 10 ].…”
Section: Feline Oral Squamous Cell Carcinomamentioning
confidence: 99%
“…Feline oral SCC (either in clinical patients, cell lines or immunohistochemical studies) has been used as a model for tumor hypoxia (which may be targeted to improve responses to chemo- or radio-therapy) [ 57 ] and mechanisms and treatment of bone invasion [ 51 , 58 , 59 , 60 , 61 ]. EGFR is a druggable target in HHNC [ 42 ], and the feline and human EGFR sequences are highly homologous [ 10 ].…”
Section: Feline Oral Squamous Cell Carcinomamentioning
confidence: 99%
“…For example, COX-2 has been shown to be expressed in a subset of feline OSCC biopsies [ 16 ]. Additionally, feline OSCC cell lines express COX-2 and STAT3 (a transcription factor important in inflammation and tumor progression), and have demonstrated sensitivity to COX inhibitors [ 17 , 18 , 19 ]. Although anti-inflammatory therapy has shown promise for the treatment of animal cancer, there are risks of gastric and renal toxicity; these drugs must be used with caution [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, our studies revealed COX-2 expression in both tumor epithelium and stroma with positive stroma cells identified as fibroblasts based on morphology. COX-2 expression within the stroma of feline OSCC has not been previously described, although a more recent study described COX-2 expression in all feline OSCC cell lines including a cell line derived from tumor associated fibroblasts (Martin et al, 2015). Examination of larger patient cohorts and further investigation of cell types expressing COX-2 will be necessary to determine the role of this immune mediator as a prognostic factor and therapeutic target for feline OSCC.…”
Section: Discussionmentioning
confidence: 99%